Distribution Map of Peristaltic Waves in the Chicken Embryonic Gut Reveals Importance of Enteric Nervous System and Inter-Region Cross Talks Along the Gut Axis - Shikaya, Yuuki; Takase, Yuta; Tadokoro, Ryosuke; Nakamura, Ryo; Inaba, Masafumi; Takahashi, Yoshiko (Frontiers in Cell and Developmental Biology, 2022)
Gut peristaltic movements recognized as the wave-like propagation of a local contraction are crucial for effective transportation and digestion/absorption of ingested materials. Although the physiology of gut peristalsis has been well studied in adults, it remains largely unexplored how the cellular functions underlying these coordinated tissue movements are established along the rostral-caudal gut axis during development. The chicken embryonic gut serves as an excellent experimental model for elucidating the endogenous potential and regulation of these cells since peristalsis occurs even though no ingested material is present in the moving gut. By combining video-recordings and kymography, we provide a spatial map of peristaltic movements along the entire gut posterior to the duodenum: midgut (jejunum and ileum), hindgut, caecum, and cloaca. Since the majority of waves propagate bidirectionally at least until embryonic day 12 (E12), the sites of origin of peristaltic waves (OPWs) can unambiguously be detected in the kymograph. The spatial distribution map of OPWs has revealed that OPWs become progressively confined to specific regions/zones along the gut axis during development by E12. Ablating the enteric nervous system (ENS) or blocking its activity by tetrodotoxin perturb the distribution patterns of OPWs along the gut tract. These manipulations have also resulted in a failure of transportation of inter-luminally injected ink. Finally, we have discovered a functional coupling of the endpoint of hindgut with the cloaca. When surgically separated, the cloaca ceases its acute contractions that would normally occur concomitantly with the peristaltic rhythm of the hindgut. Our findings shed light on the intrinsic regulations of gut peristalsis, including unprecedented ENS contribution and inter-region cross talk along the gut axis.